Loss Model for Gallium Nitride DC-DC Buck Converter - Rushi P Patel (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
In recent years, more research has been done on Enhancement Mode Gallium Nitride (eGaN) converters, as the world is moving towards more power efficient converters. Power converters play a major role in efficiently controlling and converting electric energy used by machines, systems, and everyday products. The process to make converters more efficient was complicated and slow in the twentieth century. One of the important aspects in power electronics is to evaluate different losses and minimize losses to achieve high efficiency of the converter. With help of simulation tools such as MATLAB and LTspice, this process has become much faster and reliable in the modern era. A model for estimating power losses for eGaN DC-DC buck converter (12V/1.2V) is illustrated in this paper. This loss model was calculated for different frequencies, and compared experimentally and theoretically. This paper also investigated the constant variables, which help realize the difference between theoretical and experimental losses in eGaN DC-DC buck converter. Pre-prints of this article have been previously made available [1-4].
Keywords: Gallium Nitride; eGaN; DC-DC; Buck Converter; Loss Model